(untitled) (Global Journal of Management and Business Research, 2019)
This paper is an attempt to analyze the consumers#x2019; perception of various types of advertising media and to know which media is preferred most regarding respondents#x2019; age, gender, and occupation. A sample of 150 respondents from different areas of Chittagong city has been surveyed through a structured questionnaire from June to October 2018. Descriptive Statistics, reliability test, SPSS software has been used to analyze and results show that Internet was the first preferred media for all types of respondent and TV was the immediate choice. According to profession analysis, the newspaper has been preferred most by the business person (52.94%), and TV (50%) was the most favorite media for housewives. Media preferences also differ according to age; young has been addicted to the internet (65%) most whereas mid and aged people like TV (80%) and newspaper (20%) most. Regarding their perceptions to all types of media was positive but some negative perception has been found mostly on trust (mean value=3.15), and they don#x2019;t think that advertisements present a real picture (mean value= 3.18) of the product being advertised. If the company or advertisers recover the shortcomings by enhancing the genuineness of advertising, consumers perception regarding advertising media will be more positive.